The Stereotyping Representation of Kensi Blye’s Character in Television Crime Drama Series NCIS: Los Angeles - Nobella Indradjaja; Chamdani Chamdani; Syafi'i Syafi'i (Lingua Cultura, 2022)
The research discussed a stereotyping representation of Special Agent Kensi Blye, one of the female characters in the crime drama series ‘NCIS: Los Angeles series’. In the crime drama genre, a very masculine genre, the notion of a female character having masculine traits was common. Another issue was how the other male characters in the television show saw Kensi Blye. Their willingness to openly accept that Kensi Blye had more masculine traits than her feminine traits would be discussed. To analyze the representation of Kensi Blye, the three-dimensional framework was used as the approach. The research data were gathered from the utterances expressed by Kensi Blye’s co-workers about Kensi. The textual analysis would be the analysis of obtained data using a social actor network. Then, the resulting data would be analyzed using the feminine and masculine traits to find out how the other co-workers represent Kensi Blye’s character. The finding suggests that as the only female field agent, Kensi Blye seems to have a strong character, but in certain situations, her male co-workers still question her femaleness. The stereotyping of femaleness in female characters is inevitable even in the masculine genre of television cinema.